Interim Effective Tax Rate Estimates and Internal Control Quality - McGuire, Sean T.; Neuman, Stevanie S.; Rice, Sarah C. (Contemporary Accounting Research, 2020)
ABSTRACT This study examines whether the volatility of interim estimates of the annual effective tax rate (ETR) provides ex ante information about the quality of firms' internal control environments. Recent research suggests that some firms selectively disclose internal control weaknesses (ICWs). Given the negative consequences associated with ICWs, it is important for capital market participants to be able to identify firms with ineffective internal controls in a timely manner. We find that firms with more volatile annual ETR estimates are more likely to report both tax‐ and nontax‐related ICWs in the current year. Our results also indicate that the volatility of annual ETR estimates declines following the remediation of tax‐related ICWs, but not following the remediation of nontax‐related ICWs. In addition, we find that ETR volatility in the current year is associated with the likelihood that a firm will report an ICW in the following year. Finally, we provide evidence that the volatility of annual ETR estimates is associated with the likelihood that a firm has an undisclosed ICW. In combination, our results suggest that the volatility of interim estimates of the annual ETR provides an ex ante signal of the likelihood that a firm's internal controls are ineffective.